An egg thief? : Oviraptor discovery - Eason, Sarah (Eason, Sarah. Fossils uncovered!, 2022)
Presents a graphic novel detailing paleontologist Mark Norell's discovery that Oviraptors and other meat-eating dinosaurs laid eggs. Includes back matter on dinosaurs and paleontology, a glossary, and additional resources.